Los olvidados deseantes del Darién en busca del Norte (2021)
The autonomy of migrations is a performative action of resistance and reconstruction of life on the idea of new identity and social emergence on the edge.The collective subjectivity of autonomy in places of transit and territoriality as a physical border is the result of the dynamics agentic by people who have beenvictims of hegemony and dispossession produced by violence, war, persecution, and the desire to mobilise and seek refuge and “lived life” (Valera, 2019). Thisarticle then offers a critical reflection on mobility with respect to the migration crisis in a non-place known as the Darien Pass, with the aim of proposinganalytical rationales that contribute to the debate on the impulses that mobilise autonomy at the border and how intersectionality and what I call in this reflectionsupra-intersectionality overshadow the hopeful desire for a North in the South